The diosmin antioxidant effect: an integrative review - Santos, Amanda Francielle; Machado, Rafaela Ribeiro; Mendes Neto, José Marden; Menezes, Míriam Geisa Virgens; Silva, Gilmara Beatriz Andrade da; Santos, Sandra Lauton (ABCS Health Sciences, 2018)
Oxidative stress is related to the development of multiple diseases and some studies objective to identify the effect of natural substances in lesions caused by it. One of these substances is Diosmin, a flavonoid found in citric fruits. The objective of this study was to identify through the literature the anti-oxidative effect of Diosmin. It is a descriptive and bibliographic study of integrative revision, based on articles which discussed the researched topic published between 2013 and 2017 using the electronic database PubMed and Bireme. 9 articles were analyzed. The studies evaluated show that the use of Diosmin rises the activity of enzymes which fight against oxidative stress, as catalase, superoxide dismutase and glutathione. There was reduction of the concentration of malondialdehyde. It was proved with this study that Diosmin contributes to the fight against lesions caused by the unbalance between the redox status, stimulating the rise of activity of enzymatic anti-oxidants and reducing the production of malondialdehyde, collaborating to the reduction of damage to tissues generated by stress oxidative.